Measuring resilience in the food-energy-water nexus based on ethical values and trade relations. (1st October 2022) - Schlör, Holger; Venghaus, Sandra
Graphical abstract: Highlights: German Resilience Index (GRI) for measuring socio-economic-ecological resilience. The GRI is based on the German SDGs and universal ethical values. Development of the 'resilience space function' based on the resilience factor k. Germany is at a level of roughly 75% (GRItotal  = 0.747) of its way to resilience. With a GRIenergy  = 0.568, the energy sector is farthest away from resilient development. Abstract: The challenges of the 21st century require resilient societies and a robust international regulatory framework [1] . The current disruptions to the global framework (most notably by the Covid-19 pandemic and the war on Ukraine) as well as the historic experiences especially of the Great Depression and the Lehman crisis (Annex II) elucidate the importance of the UN Sustainable Development Goals (SDGs) as a global regulatory framework. The SDGs provide new targets for resilient development. In this paper we set specific focus especially on SDG 17 "Partnerships for the Goals" and its aim of a free multilateral trading system (Annex I, SDG 17.10-17.12) for sustainable development [2] . Against this background the German Resilience Index was developed as a new measure for defining the resilience of the German society based on the SDGs including the explicit consideration of trade dynamics. The German Resilience Index (GRI) enables an analysis of the extent to which Germany has succeeded in building socio-economic-ecological resilience to defy the storms of globalization. The index is based on the German Sustainable Development Goals and the defined targets, considering also ethical values derived from the Universal Declaration of Human Responsibilities of the InterAction Council and trade relations as corner stones of resilient development. The analysis thus provides a first approach for systematically considering the impact of Germany's intensive participation in globalization and the ethical values of the German Sustainability Strategy and its SDGs. The results are important for the political decision-making process and the political as well as social discourse about the future course of sustainable, and thus resilient, development in Germany.